Construction of 0D CeO2/2D MnO2 heterostructure with high electrochemical performance. (1st October 2019) - Peng, Ruichao; Zhang, Honglei; Gui, Lin; Zheng, Yu; Wu, Zaikun; Luo, Yunbai; Yu, Ping
Abstract: The rational design of electrode material is crucial for the pursuing of energy storage device with high performance. Single active material always shows the limitation as electrode material, thus utilizing the synergistic effect between two components to construct the nanocomposite would be a good choice to optimize the electrochemical performance. In this work, a series of CeO2 nanoparticles/MnO2 nanosheets composites with diverse molar ratios are synthesized. 0D CeO2 nanoparticles are homogeneously dispersed on the 2D MnO2 nanosheets and the synthesis mechanism is studied in detail. MnO2 nanosheets with a layered structure offer abundant ion transport channel and can shorten the ion transport path. Besides CeO2 nanoparticles between the MnO2 layers which avoiding the tight stack can further accelerate the ion diffusion and bring out more active sites. With the synergistic effect, the composite CeO2 /MnO2 shows the highest capacitance (580.1 F/g at a current density of 0.5 A/g) as well as an excellent cycling performance (95.8% capacitance retention after 10, 000 cycles). The superior electrochemical performance makes this composite a promising candidate electrode material for supercapacitor application. Graphical abstract: Image 1